An integrated model of E-Government adoption the case of electronic tax filing among Indonesian corporate taxpayers - Aditiawarman, Umar; Kartiwi, Mira (IIUM Press, International Islamic University Malaysia, 2017)
Electronic Tax Filing or e-filing system has been regarded as one of the important egovernment initiatives to optimize the tax returns for a country. Indonesian government has put huge investment on the development of e-filing system and infrastructure, yet the rate of adoption is still low. Directorate General of Taxation (DJP) as e-filing service provider should have considered several aspects in increasing number of e-filing service subscribers including system, individual, government and social characteristics. Therefore, this study aims to explain e-filing acceptance and use among the corporate taxpayers by adopting several prominent technology adoption frameworks and theories such as Technology Acceptance Model (TAM), Innovation Diffusion Theory (IDT) and Perceived Characteristics of Innovating (PCI) as well as incorporating relevant factors such as trust, risk, security control, privacy protection and reputation into the research model. To better understand about e-filing implementation, a mix method approach involving survey study and semi-structured interview were conducted. A total of 156 respondents from different corporations participated in the survey study.